Effect Operation Strategy on Performance - Fien Zulfikarijah; Muhammad Raja Khwarizmi (Universitas Muhammadiyah Malang, 2023)
The aim of this research is to determine the operational strategies and business performance of entrepreneurial students, as well as to analyze operational strategies on business performance. This research was conducted on entrepreneurial students in Malang consisting of students from UB, UM Malang, Poltek, UMM, Unisma and UIN Malang. The population is students who are actively running businesses with an unknown number. Sample The sample was taken from 25 entrepreneurial students at each university, so that the total sample was 150 which was considered to represent all entrepreneurial students. The sampling technique was accidental sampling for entrepreneurial students in tertiary institutions. The analysis tool uses an interval scale and regression with SPSS. The research results show that the operation strategy and business performance of entrepreneurial students is very good, the operation strategy (cost, quality, delivery and flexibility) influences business performance.